Sources of DNA for detecting B cell monoclonality using PCR. Issue 6 (June 1994) - Diss, T C; Pan, L; Peng, H; Wotherspoon, A C; Isaacson, P G
Abstract : AIMS--To evaluate the polymerase chain reaction (PCR) demonstration of clonal immunoglobulin heavy chain gene rearrangements using routinely prepared, unstained, and stained formalin fixed, paraffin wax embedded tissue samples. METHODS--Extracts from (a) fresh frozen tissue samples, (b) unstained, and (c) haematoxylin and eosin stained formalin fixed, paraffin wax embedded 5 microns tissue sections from 42 cases of low grade B cell lymphoma, all shown to be monoclonal by Southern blot analysis, were analysed using PCR. Two regions of the variable segment of the immunoglobulin heavy chain gene were amplified (framework 2 to joining region [Fr2/JH] and framework 3 to joining region [Fr3/JH]). Twelve samples of reactive lymphoid tissue were studied as controls. Products from each case were directly compared on polyacrylamide gels. RESULTS--Using both primer combinations, monoclonality was detected in 38 of 42 (90%) cases using fresh material, 37 of 42 (88%) using unstained paraffin wax embedded samples, and in 35 of 42 (83%) cases using haematoxylin and eosin stained sections. No false positive results attributable to fixation, processing, or staining were identified, although the efficiency of amplification using the Fr2/JH primers was significantly reduced. CONCLUSIONS--PCR determination of B cell clonality using paraffin wax embedded material is sufficiently sensitive and reliable for use as a routine diagnostic adjunct to conventional morphological and immunocytochemical assessment of lymphoproliferative disease.